2015
DOI: 10.12681/mms.1440
|View full text |Cite
|
Sign up to set email alerts
|

New Mediterranean Biodiversity Records (July 2015)

Abstract: The Collective Article ‘New Mediterranean Biodiversity Records’ of the Mediterranean Marine Science journal offers the means to publish biodiversity records in the Mediterranean Sea. The current article is divided in two parts, for records of native and alien species respectively. The new records of native species include: the neon flying squid Ommastrephes bartramii in Capri Island, Thyrrenian Sea; the bigeye thresher shark Alopias superciliosus in the Adriatic Sea; a juvenile basking shark Cetorhinus maximus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…The specimen was carefully removed from its cover and transported to the research premises of HCMR-IMBBC at Thalassokosmos (Gournes, Heraklion, Kriti) where it is being kept in the experimental aquaria of IMBBC. Morphology-based characteristics, depth and substrate type agree with the findings of Katsanevakis et al (2014) and Tsiamis et al (2015). The first record…”
Section: Gerovasileiou and D Poursanidissupporting
confidence: 81%
See 1 more Smart Citation
“…The specimen was carefully removed from its cover and transported to the research premises of HCMR-IMBBC at Thalassokosmos (Gournes, Heraklion, Kriti) where it is being kept in the experimental aquaria of IMBBC. Morphology-based characteristics, depth and substrate type agree with the findings of Katsanevakis et al (2014) and Tsiamis et al (2015). The first record…”
Section: Gerovasileiou and D Poursanidissupporting
confidence: 81%
“…It was reported in the Mediterranean Sea from the Kas Peninsula (Yokes & Galil, 2006). In 2009, the species was recorded along the Lebanese coastline (Nader & Indary, 2011), later in 2010 at Antakya, south-eastern coast of Turkey (Turan et al, 2011), in 2014 and 2015 in Kastellorizo, Greece (Latsoudis in Tsiamis et al, 2015), in Kriti (Dounas & Krystalas, 2016, present article), in Rodos Island (Kondylatos & Corsini-Foka in Crocetta et al, 2015) and in Gökova Bay (Yapici et al in Katsanevakis et al, 2014). According to Turan et al (2011), D. setosum may have been transported to Antalya Bay by vessels arriving from the Suez Canal or possibly by sea currents flowing from the northern part of the Gulf of Suez.…”
Section: First Record Ofmentioning
confidence: 97%
“…The diagnostic features and substrate agree with the find- in Katsanevakis et al (2014a), respectively. The spines were black as in Latsoudis in Tsiamis et al (2015) (no gray spines were observed) and the depth corresponds to another publication (e.g. Yokeş & Galil, 2006).…”
Section: A Zenetos a And M Giavasimentioning
confidence: 57%
“…It occurs throughout the Northwestern Pacific (Japan to Australia and Fiji), the Indo-Pacific, the East African coast and the Red Sea. After its first occurrence in the Mediterranean Sea in 2006 around Kaş Peninsula (Turkey), it has been subsequently reported from Lebanon in 2009, Turkey in 2010 and 2014 and Greece (Kastellorizo Island) in 2014 (Latsoudis in Tsiamis et al, 2015).…”
Section: A Zenetos a And M Giavasimentioning
confidence: 99%
“…In the Mediterranean Sea, and as far as we are aware, the first record dates to 1878 [53]. So, the increased frequency of reports in the Mediterranean Sea and in the northeastern Atlantic may simply reflect the increased research efforts of current times [48,49,[51][52][53][57][58][59] However, all these facts do not imply that climate change is not inducing, or will not induce, a poleward range expansion of oceanic puffer populations. In the case of the Guadiana estuary, both climate change and the disruption of natural river flow caused by the Alqueva dam might have contributed to the presence of oceanic puffer specimens in the estuary in tandem with the proximity of the Algarve to subtropical regions.…”
Section: Discussionmentioning
confidence: 99%